2000
DOI: 10.1002/1099-0488(20001101)38:21<2714::aid-polb20>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Water sorption and activation energy in polyimide thin films

Abstract: The water sorption behavior and the activation energy were investigated for various chemical structure polyimide thin films; BPDA‐PDA, BPDA‐ODA, PMDA‐ODA, and 6FDA‐ODA. The activation energy for the water diffusion varied in the range of 5.53 to 9.27kcal/mol, and was in the increasing order: BPDA‐PDA < BPDA‐ODA < PMDA‐ODA < 6FDA‐ODA. BPDA‐PDA and BPDA‐ODA polyimide films showed relatively well‐ordered morphological structure, which results in relatively low diffusion coefficient and high activation energy. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 19 publications
0
46
0
Order By: Relevance
“…These were described in our previous literature. [11][12][13][14][15][16][17][18][19] All the sorption isotherms were analyzed with Fick's second law given by Crank and Park 20,21 :…”
Section: Water Sorptionmentioning
confidence: 99%
See 4 more Smart Citations
“…These were described in our previous literature. [11][12][13][14][15][16][17][18][19] All the sorption isotherms were analyzed with Fick's second law given by Crank and Park 20,21 :…”
Section: Water Sorptionmentioning
confidence: 99%
“…This suggests that there may be no apparent morphological difference in the isomeric BPDA-DDS polyimide thin films. [15][16][17][18][19] From the water sorption results, it was found that the polyimide thin films with para-oriented linkage (p, p,pЈ, or p,pЈ) showed relatively lower diffusion coefficient and water uptake than the corresponding polyimide thin films with meta-oriented linkage (p, p,mЈ, or m,mЈ). In addition, both water uptake and diffusion coefficient are quite different from each other depending on the sort of polyimide.…”
Section: Water Sorptionmentioning
confidence: 99%
See 3 more Smart Citations